The Effect of Information and Communication Technology on Economic Growth: Arab World Case - Hodrab, Rami; Maitah, Mansoor; Smutka, LuboÅ¡ (International Journal of Economics and Financial Issues, 2016)
Information and communication technology (ICT), population growth, gross capital formation, openness and inflation are frequently well-thought-out as important drivers of economic growth in all countries especially for developing ones and so for Arab countries in our case. This paper aims to examine the effect of these factors on 18 selected Arab countries’ economic growth during the period from 1995 to 2013. Econometric analysis using panel regression has been adopted to test this impact. Ordinary least square model, random effects and fixed effects model have been applied for the study sample of 341 observations, and in order to choose the appropriate model, Hausman test has been used. For our analysis we used a basic model that includes the dependent variable GDP per capita as an economic growth factor and the main concerned independent variable info density index that represents the capital and labor stock of ICT. Then we extended the model with other standardized macroeconomic control variables mentioned above and applied the three methodologies of regression. The outcomes illustrate that ICT has positive impact on the selected Arab countries’ economic growth as well as the other factors except for inflation which has a negative impact on economic growth for these countries. The impact degree of ICT on economic growth is less than that of other countries especially emerging and developed economists. Keywords: information and communication technology (ICT), ICT index, population growth, gross capital formation, openness, inflation, economic growth, Arab countries JEL Classifications: C33, E22, O47